Evaluation of prebent miniplates in fixation of Le Fort I advancement osteotomy with the finite element method. Issue 8 (October 2015) - Coskunses, Fatih Mehmet; Kan, Bahadir; Mutlu, Ibrahim; Cilasun, Ulkem; Celik, Talip
Abstract: The stability of segments after Le Fort I osteotomy first attracted the researcher's interest when the surgical concept was conceived. Prebent plates are the ultimate modification of plate systems in craniofacial surgery; they have two right angles and are available in different lengths for use in maxillary advancement surgery. For this research, cone-beam computed tomography (CBCT) images of a male patient were obtained and scanned, and a 3D maxillary bone was created. Conventional Le Fort I osteotomies with 5 and 10 mm advancements were performed on both the cortical and trabecular bone using the Surgical Simulation Module of Mimics software; 1.7 mm Leibinger standard orthognathic 5-hole L plates and 1.7 mm Leibinger orthognathic advancement 11-hole prebent plates were adapted to the fragments. Displacement of the segment, the von Mises (VM) stresses (on the titanium miniplates) and the maximum principal (MP) stresses (on the bone) were evaluated for each configuration. Prebent plates offer a good alternative to the conventional two plate system, except in operations where maxillary advancement exceeds 5 mm. Surgical procedures that include advancement exceeding 5 mm or vertical position changes remain controversial and further studies are needed.